Standardization Of Dakak-Dakak Recipe In Simabur Sub District Pariangan District Tanah Datar Regency - Septia Rahmi; Elida Elida (Jurnal Pendidikan Tata Boga dan Teknologi, 2021)
This research is to find the standart recipe of dakak-dakak recipe, include the quality of dakak-dakak. The methods of this research is Mix Method, that is combine a qualitative research and the quantitative research. This research was conducted in Nagari Simabur, Tanah Datar Regency from May 6, 2019 to May 31, 2019. The data sources used in this study were qualitative data sources obtained from people who are good at making dakak-dakak, and quantitative data sources were obtained from 10 people. Limited panelists, namely the Desa Simabur community who are experts in making dakak-dakak. Based on the results of quantitative research, it was found that the number of recipes that had been converted to grams as units of measure. From the results of the organoleptic test conducted, it was found that the quality of the dakak-dakak included: shape of the dakak-dakak (round hollow), shape (uniform), shape (neat), color (yellowish white), color (uniform), aroma (fragrant of flour rice), texture (brittle), and taste (savory).